Opinions of students of Special Education concerning pedagogical internship - Agnieszka Maria Pawlak-Kindler (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article presents results of studies conducted among female students of the special education at the Maria Curie Skłodowska University in Lublin. The research concerned the realisation of pedagogical practice valid for this specialization. The results were presented to headmasters and teachers (internship supervisors) during a meeting concerning increasing the quality of internship realised by the University. The aim was to develop common solutions and postulates which can effectively modify current activities in the field of the practical preparation of future special education teachers.